Anton August Heinrich Lichtenstein’s (1794) Catalogus Rerum Naturalium Rarissimarum, pars secunda. Facsimile edition and annotated translation - Geiger, Daniel L. (Zootaxa, 2022)
The new species of Lichtenstein’s catalog (1794: part 2) were discussed by Geiger (2003). Here a facsimile edition and full translation of the work is given. Additional insights into select Lichtenstein species are provided. Tentative identifications include Mya papyracea Lichtenstein, 1794 as a member of Thraciidae, Helix porphyrostoma Lichtenstein, 1796 from Ambon as a member of Planorbidae and Helix australasiae Lichtenstein, 1794 from Tahiti as a Partula sp. Trochus tahitiensis Lichtenstein, 1794 is here designated as a nomen oblitum with Trochus histrio Reeve, 1861 [1842 in error] as its nomen protectum. Oliva brasiliensis Chemnitz and Murex galea Chemnitz (now Coralliophila galea) were first made available by Lichtenstein (1794), not by Schumacher (1817) and Dillwyn (1823), respectively. Olivancillaria brasiliensis (Lichtenstein, 1794) is senior synonym of O. urceus (Röding, 1798).